Provenance and annotation of data and processes : 4th International provenance and annotation workshop, IPAW 2012, Santa Barbara, CA, USA, June 19-21, 2012, Revised Selected Papers - Frew, James; Groth, Paul (Lecture Notes in Computer Science, 2012)
This book constitutes the revised selected papers of the 4th International Provenance and Annotation Workshop, IPAW 2012, held in Santa Barbara, CA, USA, in June 2012. The 14 full papers, 4 demo papers and 12 poster papers presented were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on documents databases; the Web; reconstruction; science applications; and demonstrations.